Failure on Wiji Thukul Literature Practices: Study of Cultural Production Arena On Pierre Bourdieu - Panji Kuncoro Hadi, Suyitno, Retno Winarni, Nugraheni Eko Wardani (International Journal of Advanced Science and Technology, 2020)
This study aims to explain the literary practice of Wiji Thukul. Practice requires a relationship between habitus, capital and arena which makes education factor become very important. The intended education includes informal, non-formal education and formal education as cultural capital or as habitus maker in somenone’s life. Wiji Thukul’s habitus as a writer can be taken as an example. This research focus on whether his education as one of his capitals influence his practice, especially in the arena of Indonesian literature which require a certain rules of the game and whether education as one of the habitus aspects influence Wiji Thukul’s habitus as a writer. This descriptive qualitative study uses Pierre Bourdieu’s theory of cultural production arena to explain the above problems. Literature study is used to collect the data from; The Poetry Anthology Book by Wiji Thukul “I Want to Be a Bullet” ( Aku Ingin Jadi Peluru), the Poetry Anthology by Wiji Thukul “Grass Root Song” (Nyanyian Akar Rumput) and the Tempo Investigation Report Book. Based on the predetermined data sources, the collected data were analyzed with the arena theory of cultural production. The result shows that education plays a role in Wiji Thukul's literature practice especially in forming his habitus as a poet but it doesn form his cultural capital. His education background as a high schools’s dropped out influenced his habitus as a poet but not his cultural capital.